MEANING IN THE PROCESS OF SIGNIFICATION BY THE ADVERTISEMENT OF HONDA - Nicholas J.H. Wibowo; Samuel Gunawan (Kata Kita: Journal of Language, Literature, and Teaching, 2016)
This study mainly deals with the process of signification in order to reveal how meaning is created by the advertisement of Honda HR-V 2014 through the use of expressions. In this study, “Meaning” is an integrated form consisting the three elements which are denotative form, connotative form, and myth form. Using qualitative content analysis (Schreier, 2012), the writer did this study based on Barthes’s process of signification (1987) and Peirce’s indexicality (1931-58). From the analysis, the writer found out that meaning is created by indexicality. The index connects the product and the traits that the product possesses. Then, the use of expressions in the advertisement visualises the index of the product. The index which was visualised by the use of expressions which produces denotative meaning and connotative meaning. Those denotative meaning and connotative meaning are perceived by the audiences and creates myth which naturalises the index itself. It can be concluded from this study that meaning is created by the index and has undergone several steps in order for audiences to perceive the myth and become unaware of the index.